INTERVENSI UNTUK MENINGKATKAN SELF EFFICACY PERAWAT: LITERATURE REVIEW - M Martono Diel; Tri Nur Kristina; Devi Nurmalia (Jurnal Surya Muda, 2022)
Self efficacy is the belief in the ability to perform and fulfill goals. Nurses need appropriate interventions to improve performance that can help patients heal. This study aims to provide an overview of interventions that can support self-efficacy in nurses. The literature search in this study used an electronic database search that included Science Direct, Wiley, PubMed, and Google Schoolar. The articles used in this study were published from 2011 to 2020 full text in English and according to the topic. Providing education to nurses, leadership training, health coaching management, simulation, and communication training can increase the self-efficacy of nurses in the experimental group compared to the control group. Thus it can be concluded that the intervention in the form of education and training can increase the self-efficacy of nurses. Nurses with high self-efficacy can improve their ability to face challenges and complete tasks at work.